SIMULADOR DE CRESCIMENTO E PRODUÇÃO DE Pinus taeda L. EM NÍVEL DE ÁRVORE INDIVIDUAL - RETSLAFF, FRANCIÉLE MARIA DE SOUZA (2023)
The aim of this research was to build a forest growth and production simulator at the individual tree level, distance-independent, for unthinned Pinus taeda L. stands. The data used came from 537 permanent plots, aged between 3 and 22 years, distributed in stands located in the region of Telêmaco Borba, state of Paraná, Brazil. Models were tested to construct site curves and to express the hypsometric relationship. Distance-independent competition indexes were tested and inserted into survival models and individual tree models to predict future diameter and total height. The logistic model was used to predict the annual survival of individual trees, initially considering regular and irregular mortality, including trees damaged by the capuchin monkey (Sapajus nigritus Goldfuss, 1809), and then only regular mortality. The Chapman-Richards biological model was selected and the site curves were constructed using the algebraic difference method, while the Nogueira (2003) model was the most appropriate for estimating total height at the various ages. The models for projecting diameter at breast height and total height for P. taeda stands provided good projections, depending on the variable itself at the current age (DAP1 and h1), projection age (I2), basal area (G ha-1), site index (S) and competition index (CI). Estimated survival was underestimated at older ages, indicating that the model was unable to assess survival at ages above 14, the main cause of this behavior being that the database was not robust enough to express the stand from that age onwards. In the end, using all the adjusted equations, a simulator was built in the C# programming language that makes it possible to project the various dendrometric averages, individual volumes, total volume and wood assortments per hectare. The cut-off point of 0.83 showed better projections at older ages (12-14 years). The equations generated in this research are recommended for P. taeda data without thinning for projections up to a maximum age of 14 years. The developed simulator is capable of making tree-level projections and can carry out simulations quickly and practically, facilitating the application of individual modeling, however, like any forest growth and production simulator, the first version built needs to evolve in its development and improvement to make it more accurate and flexible.